THE ART OF INDIVIDUALIZED HOMEOPATHY IN TREATING ADJUSTMENT DISORDER: INSIGHTS FROM A CASE SERIES - DR. SNEHA ASHOKKUMAR AGRAWAL; DR. JIGNESH PATEL (The Bioscan, 2025)
Every society's progress and productivity, as well as a healthy and happy life, rely on good mental health. Homoeopathy prioritizes mental wellness in the treatment of both physical and mental illnesses. The Homoeopathic approach to health is mostly linked to its understanding of the mind in general. They commonly believe that the body and mind are inextricably linked and have a direct impact on one another. Homoeopaths base almost all of their prescriptions on the ill person's bodily and psychological symptoms. Psychological symptoms are frequently used to guide the selection of the appropriate medicine.